Steels : microstructure and properties - Bhadeshia, H. K. D. H. (Harshad Kumar Dharamshi Hansraj), 1953- (Elsevier, Butterworth-Heinemann, 2006)
The most comprehensive and up-to-date textbook on the microstructure and properties of steels.